Work-Integrated Learning Policy in Alberta: A Post-Structural Analysis - Arney, Noah D.; Krygsman, Hilary P. (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2022)
In late 2020 the Government of Alberta’s Ministry of Advanced Education sent a guidance document to Alberta post-secondary institutions to lay out how work-integrated learning was to be conducted. This document also informed the institutions that work-integrated learning should be included in all future program proposals. The guidelines were sent without the context or purpose stated. This paper applies Carol Bacchi’s “What’s the Problem Represented to be” post-structural policy discourse analysis to the Ministry of Advanced Education guidelines. There is a broad consensus in work-integrated learning research that work-integrated learning is beneficial for participants beyond employment outcomes. However, this analysis shows the Ministry of Advanced Education’s representation of the problem displays an assumption that the purpose of work-integrated learning is to improve labour market outcomes. The analysis also spotlights that the likely effects of the policy have more to do with making work-integrated learning programs easier to assess than to improve student education. This paper proposes an alternative framework that would integrate the constructivist and humanistic origin of work-integrated learning and allow institutions to develop appropriate experiential learning components for their programs while still standardizing work-integrated learning components across and within institutions. This proposed framework can improve work-integrated learning programs in Canada by widening the focus beyond human capital theory.